2009
DOI: 10.1590/s1413-78522009000100006
|View full text |Cite
|
Sign up to set email alerts
|

Lesão meniscal por fadiga

Abstract: Objective: The purpose of the present study was to review a group of patients with meniscal injuries resulting from structural failure unrelated to trauma or degenerative problems to which was given the name "meniscal injury due to fatigue". Material and Method: Evaluations were made on 140 patients with meniscal injuries without any apparent cause, who were therefore considered to have meniscal injuries due to fatigue. Among these, 85 patients were male and 55 were female. The medial meniscus was the most aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…3 We studied 87 patients with meniscal fatigue injury, without detectable cartilage injury. 7,8 All patients in the present study had MRI and radiographs that were efficient for the diagnosis of absence of cartilage lesions, because only in one case we found signs of chondral injury in the arthroscopy that had not been diagnosed in the evaluation by image.…”
Section: Treatmentmentioning
confidence: 80%
“…3 We studied 87 patients with meniscal fatigue injury, without detectable cartilage injury. 7,8 All patients in the present study had MRI and radiographs that were efficient for the diagnosis of absence of cartilage lesions, because only in one case we found signs of chondral injury in the arthroscopy that had not been diagnosed in the evaluation by image.…”
Section: Treatmentmentioning
confidence: 80%
“…They can also occur due to degeneration or spontaneously due to the progressive structural failure, which is known as the meniscal fatigue injury. 17 Knee arthroscopy is the gold standard investigation, which can simultaneously treat the meniscus disorders. 3 The graft sizing, precise positioning and fixation are the three prerequisites for successful allograft meniscal transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Age below 18 years was considered an exclusion criterion. In the study of Camanho 4 the prevailing average was 50-59 years (34.7%) among 435 patients included, where 261 were male (60%) and 174 female (40%).…”
Section: Discussionmentioning
confidence: 99%
“…According Camanho 4 the medial and lateral meniscus is injured in 81.8% and 18.2% of cases, respectively. In this research it was found 37 tears of the medial meniscus (61.6%), 16 with lateral meniscus injuries (26.7%) and in seven (11.7%) had both menisci injured.…”
Section: Discussionmentioning
confidence: 99%